PENALARAN MORAL ANAK DALAM CERITA PADA MAJALAH BOBO DAN HARIAN KOMPAS - Heru Kurniawan (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
Children's stories in Bobo Magazine and Kompas Daily represent both levels of praconventional and conventional moral reasoning. From these two levels of moral reasoning, there are three stages of a child's moral reasoning, namely moral reasoning for obedience of punishment, relativist-instrument moral reasoning, and moral reasoning of a good child. Of these three moral reasoning, the dominant moral reasoning of children is the relativist-instrument and the orientation of a good child, while obedience reasoning does not dominate. This shows that mutual moral awareness of children is transactional and existential, namely children are conditioned to do good because they want to get a prize, and awareness of their desire to be good children. With the reality of such children's stories, our children who read children's stories wake up to the realization that I am doing good because of the gifts and awareness to be a good child.